Recuperación de Cr3+ del agua de curtido por precipitación con NaOH y su reactivación con ácido fórmico para el proceso de curtido a nivel piloto - Anhuaman Namoc, Bertha Beatriz (2017)
The influence of the NaOH in 98% solid and Lightan (tannin) for the process of precipitation of chromium, of the tanning water of the company Curtiembre Ecológica del Norte E.I.R.L. And its reactivation with formic acid, with the purpose of reinserting it in the process. The studies were carried out first at laboratory level, varying the concentration of NaOH in 98% solid in a concentration range of 2.5 g / L to 15 g / L and Lightan in 0.25 g / L to 15 g / L, considered by Each liter of tanning water. A removal of 99.9% of Chromium was obtained, at 7.5 g / L of NaOH in 98% solid and 0.25 g / L of Lightan. Subsequently with these quantities was scaled to pilot level where the results obtained at laboratory level were replicated. The chromic reactivation process of the precipitate was carried out with formic acid to be used in the tanning process